Mylabris: a review of its biological characteristics, chemical composition, pharmacological, toxicology, pharmacokinetics, and marketed drugs - Cai, Qingqing; Yan, Jing; Li, Xinghong; He, Lihua; Xie, Shan; Yang, Yaxin; Wu, Hongwei; Zhang, Fangbo (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceMylabris (“斑蝥’’), derived from the dried bodies of the Chinese blister beetles Mylabris phalerata Pallas and Mylabris cichorii Linnaeus, which has the effect of breaking blood and chasing blood stasis (“破血逐瘀”), dispersing knots and eliminating symptoms (“散结消癥”), and attacking poison and eroding sores (“攻毒蚀疮”).AimThis review provides the firstly comprehensive summary of mylabris, covering its biological characteristics, chemical composition, pharmacological, toxicology, pharmacokinetics, and clinical use.Materials and methodsA systematic literature search was conducted in databases (“Web of Science”, “PubMed”, “Google Scholar”, “CNKI”, and “WanFang”) using the following query (“Mylabris phalerata Pallas” OR “Mylabris cichorii Linnaeus” OR “Mylabris” OR “Banmao” OR “Cantharidin”) AND (“Pharmacology” OR “Toxicity” OR “Pharmacokinetics” OR “Marketed drugs”), to identify literature published between 2000 and 2025, focus on referring to 2015–2025. Articles with methodological defects (e.g., sample size less than 5 per group, no standardized purity detection method used), incomplete data (e.g., no access to the original literature, lack of key data values), and ethical problems (no declaration of ethical approval) were excluded. Online websites were also used, including https://ydz.chp.org.cn/#/main (Chinese Pharmacopoeia), https://www.nmpa.gov.cn/datasearch/home-index.html#category=yp (National Medical Products Administration), to obtain information on mylabris- or cantharidin-marketed drugs. Chemical structures in SMILES format were retrieved from the PubChem, and two-dimensional chemical structures were generated using ChemDraw 22.0.0.ResultsThe major components of mylabris include terpenoids, metallic elements, fatty acids, and peptides. Pharmacological research have demonstrated its anticancer, antithrombotic, and antiviral effects in preclinical study, as well as insecticidal and antifungal in agriculture. Cantharidin is considered to be the main active and toxic component, which can cause gastrointestinal, cardiovascular and respiratory toxicity if used improperly. Pharmacokinetic studies reveal that orally cantharidin predominantly accumulates in the liver and kidneys, exhibiting strong irritancy and low bioavailability. Given its therapeutic efficacy, researchers have also developed various mylabris and cantharidin-based drugs in clinical setting.ConclusionMylabris has been used in traditional Chinese medicine for millennia. Now, it treats various diseases and shows development potential. Future studies should focus on four key aspects: comprehensive characterization of active components, elucidation of pharmacological mechanisms, supplementation of pharmacokinetic data, and clarification of toxicological mechanisms. This paper reviews the research progress of mylabris, bridging traditional applications and modern investigations to advance contemporary research and evaluate its therapeutic potential for human diseases.